The Fifth Column of the Soviet Union in Anykščiai Region in Interwar Lithuania - Vaičiūnas, Gintaras (Genocidas ir rezistencija, 2023)
The communist underground movement which emerged in the provinces of Lithuania during the years of independence used to be involved in anti-state subversive activities in favour of the foreign state, the USSR, already before the occupation, thus laying down the foundations of a collaborative system. The Lithuanian Communist Party was a strictly centralised organisation consisting of LCP groups, districts, regions, and units which were governed by the Central Committee of the LCP through instructors appointed by this institution of the LCP. In Anykščiai and in the adjacent Kavarskas parish the first communist groups were created by members of the Communist Party of the whole of Russia (VKP (b)); Edvardas Makštys, former secretary of the revolutionary committee of the Švenčionys district, a teacher, and Alfonsas Karosas, former commissar of the RA division and a pharmacist. The communist underground movement founded by the Lithuanian bolsheviks was expanding, and new underground communist groups started to appear both in the parish centres of Anykščiai and Kavarskas and in the villages of these parishes. Communists from Anykščiai and Kavarskas were active in cooperation, and for some time they belonged to the same LCP Anykščiai volost. The communist movement in the LCP Anykščiai-Kavarskas volost (from 1934 onwards) was small and very scarce archival data suggest that during the years of independence in Anykščiai there were only three Lithuanian and one Russian communist, all the others were Jews. In Kavarskas, only Jews were members of communist organisations. The situation in Anykščiai and Kavarskas was quite the opposite: members of Communist and Komsomol groups operating in the villages of Anykščiai and Kavarskas volosts were exclusively Lithuanians, as there were almost no Jews living in rural areas. In terms of the total number of members and supporters of communist organisations in Anykščiai (in the towns and villages) during the years of independence, the number of communists, members of the Komsomol and the international organisation for the support of the revolutionary struggle (in Russian – MOPR) was fewer than 80 persons, which was less than 1 per cent (0.58) of the population in the volost (in September 1939, a total population of the volost was 13,741 person). All in all, in 1940 there were 18 communists and about 30 members of the Komsomol and the MOPR in Anykščiai volost, and the same number (about 30) of their supporters (mostly acting as sureties for the detained communists). In 1936, 37 members of communist organisations lived in Anykščiai (some of them were serving prison sentences at the time), 33 of whom were Jews, which constituted 2.34 per cent of the Jewish community in Anykščiai (according to the data from September 1939, there were 1,405 Jews living in Anykščiai). The Lithuanian security police successfully controlled the activities of the communists, and the latter did not constitute a major source of concern for the state. Due to the low number of communists and the hostility of the majority of the population towards them, they had no means and no way of changing the government, either by election (the LCP was banned in Lithuania) or by force. The situation changed radically after the occupation of Lithuania by the Soviet Russia, when the former fifth column – members of communist organisations and their supporters, together with the representatives of the occupiers, took over almost all the most important government posts and workplaces, and set about destroying everything connected with the independent state of Lithuania and its autonomy.